2005
DOI: 10.1002/jmri.20249
|View full text |Cite
|
Sign up to set email alerts
|

Interstudy reproducibility of three‐dimensional volume‐selective fast spin echo magnetic resonance for quantifying carotid artery wall volume

Abstract: Purpose:To assess the interstudy reproducibility of a three-dimensional volume-selective, fast spin echo (FSE) magnetic resonance technique for the assessment of carotid artery wall volume, which is a marker for total carotid plaque volume. Materials and Methods:Interstudy reproducibility was evaluated in 10 subjects with evidence of carotid artery atherosclerotic disease on carotid Doppler ultrasonography. Subjects were scanned twice with an interscan time of one hour to four days. The carotid artery was imag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
1

Year Published

2006
2006
2008
2008

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 20 publications
3
19
1
Order By: Relevance
“…This is reflected by the improved detection of complex atherosclerotic plaque at 3T, as validated by histology (36), and the increased SNR, CNR, and improved image quality of the carotid images at 3T (21) as compared to 1.5T. In the current study we evaluated a GRE sequence with 0.46 mm ϫ 0.46 mm ϫ 2 mm spatial resolution, which is comparable to that employed in recent studies at 1.5T (28,29).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…This is reflected by the improved detection of complex atherosclerotic plaque at 3T, as validated by histology (36), and the increased SNR, CNR, and improved image quality of the carotid images at 3T (21) as compared to 1.5T. In the current study we evaluated a GRE sequence with 0.46 mm ϫ 0.46 mm ϫ 2 mm spatial resolution, which is comparable to that employed in recent studies at 1.5T (28,29).…”
Section: Discussionmentioning
confidence: 96%
“…FSE sequences with multiple contrast weightings are commonly used to meet these requirements, and some reports have shown reliable results with GRE sequences (27). Recent studies have shown the reproducibility of a 3D volume-selective FSE sequence in both patients with known atherosclerotic disease (28) and asymptomatic patients (29). While most prior work on carotid vessel wall imaging was performed at 1.5T using FSE techniques, the present study was conducted at 3T using a spoiled GRE (SPGRE) imaging sequence.…”
Section: Discussionmentioning
confidence: 97%
“…Most work has been performed in the carotid artery and aorta, because of its closeness to the surface and larger size, respectively. Studies with carotid MRI demonstrated an interstudy reproducibility of 4.4% 85 . A number of serial studies in humans have assessed CMR in the longitudinal measurement of aortic and carotid atheroma [86][87][88][89][90] .…”
Section: Cardiovascular Magnetic Resonancementioning
confidence: 94%
“…An additional limitation is that only one viewer was used to analyze all datasets so that no data were available on interobserver variability with this technique. However, previous work has shown the interstudy variability to be of the order of 4.5% (12,13).…”
Section: Discussionmentioning
confidence: 90%
“…In general, the benefits of reduced scan time and improved resolution need to be weighed against the consequent reduction in SNR, and the final protocol will depend on the desired clinical application. 3D carotid wall imaging also has good reproducibility (12), although this has not yet been reproduced in patients with carotid atherosclerosis (28). Finally, 3D data have the advantage that any slice orientation can be retrospectively displayed by selecting appropriate 3D voxels from it, and this can be most helpful if, for example, the carotid arteries are not parallel.…”
Section: Discussionmentioning
confidence: 99%